(3EceGd JgPjH GdceGd aj CSeGA GdQLGds - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s; (3jhSa Hf YHO GdQMef Hf jhSa, CHh GdMLGL, LeGd GdOjf GHf GdRcj CHj eMeO GdbVGYj GdcdHj GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aVd GdYGde HCUZQjg hLYd GdLGgd jVQH CUOQjg s
(3BNQgG (B:s
(3HJQLeI CjhH QLd ef Cgd GdTGe ef BNQ HGH GdgeRI s
(3fSNI QGHYIs
(3hgPG GdcJGH Cced Hg GdeDda cJGH JgPjH GdceGd ddMGaX GdeRi GdeJhaj SfI (B742 (3g` hcJGH GdMGaX GdeRj gPH ajg cJGH GdceGd aj eYQaI CSeGA GdQLGd ddMGaX YHOGdZfj GdebOSj GdLeGYjdi (B600 (3g`s
(3hGdehLhO efg GdSaQ GdChd hjMJhi Ydi YTQI CLRGA ef JLRFI GdeDds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs